Analisis Pengaruh Perceived Security dan Perceived Enjoyment terhadap Continuance Intention Pengguna ShopeePay Generasi Z di Jakarta dengan User Satisfaction sebagai Variabel Mediasi - Isia Kim Sung Wita; Nadya Fadilah; Sefrimel Angriani ZN (Indo Publishing, 2026)
This study analyzes the influence of perceived security and perceived enjoyment on continuance intention among ShopeePay users in Generation Z in Jakarta, with user satisfaction as a mediating variable. This quantitative research employs a survey method with a questionnaire distributed to 160 respondents using purposive sampling. Data analysis using PLS-SEM with SmartPLS 4.0 shows that perceived security has a positive and significant effect on user satisfaction (coefficient 0.493; p-value 0.000), perceived enjoyment has a positive and significant effect on user satisfaction (coefficient 0.483; p-value 0.000), and user satisfaction has a positive and significant effect on continuance intention (coefficient 0.365; p-value 0.000). User satisfaction partially mediates the relationship between perceived security and continuance intention (coefficient 0.432; p-value 0.000), as well as between perceived enjoyment and continuance intention (coefficient 0.422; p-value 0.000). The R² values of 0.878 for user satisfaction and 0.765 for continuance intention indicate strong predictive power. This study concludes that security and enjoyment are crucial factors in shaping satisfaction and driving continuance intention among Gen Z e-wallet users.